2016
DOI: 10.1111/adj.12415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjunctive azithromycin and amoxicillin/metronidazole for patients with chronic periodontitis: preliminary randomized control trial

Abstract: Adjunctive systemic antibiotics in the initial phase of treatment may result in improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 70 publications
12
64
4
3
Order By: Relevance
“…This ultimately emphasizes the importance of conventional SRP therapy for inducing the resolution of the inflammatory response and facilitating periodontal tissue healing. These results are also in accordance with similar studies in the literature that suggest that SRP + AMX + MTZ or SRP + AZ have no significantly greater improvements over SRP alone in full‐mouth clinical parameters . However, the clinical relevance of using full‐mouth CAL and PPD to describe treatment efficacy is highly controversial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This ultimately emphasizes the importance of conventional SRP therapy for inducing the resolution of the inflammatory response and facilitating periodontal tissue healing. These results are also in accordance with similar studies in the literature that suggest that SRP + AMX + MTZ or SRP + AZ have no significantly greater improvements over SRP alone in full‐mouth clinical parameters . However, the clinical relevance of using full‐mouth CAL and PPD to describe treatment efficacy is highly controversial.…”
Section: Discussionsupporting
confidence: 89%
“…To date, only one randomized controlled trial (RCT) has directly compared the clinical effects of AMX + MTZ against AZ after SRP for the treatment of chronic periodontitis . This study found AMX + MTZ to be superior to AZ in only one full‐mouth clinical parameter and thus, further investigations are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The growing prevalence of antimicrobial resistance has prompted the development of new antimicrobial therapeutic approaches for the treatment of biofilm-related oral diseases. In the present study, the results obtained for PPD and CAL in deep pockets in the Test group at 90 postoperative days were similar to or higher to those obtained in some studies that used antibiotics as adjuvants to SRP for the treatment of chronic periodontitis (Feres et al, 2012;Saleh, Rincon, Tan, & Firth, 2016;Silva et al, 2011).…”
Section: Immunological Monitoringsupporting
confidence: 90%
“…Furthermore, the reduction in PPD was greater in the same group. These results differ from those described in previous studies, where no signi cant differences between study groups were observed at any time points [13,18,19]. Otherwise, previous research [20,21] reported a signi cant reduction in the average PPD, consistent with this study.…”
Section: Discussioncontrasting
confidence: 66%